(3RHOI GdEOQGc aj gjFI GdCadGcs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s ((3eMeO Hf YHO Gdedc GdJejei s)
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3abO dNUJ GdcJH GdeUfaI ai Yde GdgjFI hNdUJ efgG RHOgG hdHGHgG hChOYJgG gPG GdeNJUQ GdeSei s
(3BNQgG (B:s
(3aef CQGO JMbjbgG adjQLY EdjgG hGddg GdeSJYGf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B5 - (3U(B92s
(3ajgG HYV GdQShe GdgfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B931 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B62 s
Keywords: (3Gdadcs